CircRNA_000203 enhances the expression of fibrosis-associated genes by derepressing targets of miR-26b-5p, Col1a2 and CTGF, in cardiac fibroblasts - Tang, Chun-Mei; Zhang, Ming; Huang, Lei; Hu, Zhi-qin; Zhu, Jie-Ning; Xiao, Zhen; Zhang, Zhuo; Lin, Qiu-xiong; Zheng, Xi-Long; -Yang, Min; Wu, Shu-Lin; Cheng, Jian-Ding; et al. (Scientific reports, 2017)
Circular RNAs (circRNAs) participate in regulating gene expression in diverse biological and pathological processes. The present study aimed to investigate the mechanism underlying the modulation of circRNA_000203 on expressions of fibrosis-associated genes in cardiac fibroblasts. CircRNA_000203 was shown upregulated in the diabetic mouse myocardium and in Ang-II-induced mouse cardiac fibroblasts. Enforced-expression of circRNA_000203 could increase expressions of Col1a2, Col3a1 and α-SMA in mouse cardiac fibroblasts. RNA pull-down and RT-qPCR assay indicated that circRNA_000203 could specifically sponge miR-26b-5p. Dual luciferase reporter assay revealed that miR-26b-5p interacted with 3′UTRs of Col1a2 and CTGF, and circ_000203 could block the interactions of miR-26b-5p and 3′UTRs of Col1a2 and CTGF. Transfection of miR-26b-5p could post-transcriptionaly inhibit expressions of Col1a2 and CTGF, accompanied with the suppressions of Col3a1 and α-SMA in cardiac fibroblasts. Additionally, over-expression of circRNA_000203 could eliminate the anti-fibrosis effect of miR-26b-5p in cardiac fibroblasts. Together, our results reveal that suppressing the function of miR-26b-5p contributes to the pro-fibrosis effect of circRNA_000203 in cardiac fibroblasts.